2020
DOI: 10.1093/neuros/nyaa071
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation of Abnormal Neurological Tissue Using Robotic NeuroBlate System (LAANTERN): 12-Month Outcomes and Quality of Life After Brain Tumor Ablation

Abstract: BACKGROUND Laser Ablation of Abnormal Neurological Tissue using Robotic NeuroBlate System (LAANTERN) is an ongoing multicenter prospective NeuroBlate (Monteris Medical) LITT (laser interstitial thermal therapy) registry collecting real-world outcomes and quality-of-life (QoL) data. OBJECTIVE To compare 12-mo outcomes from all subjects undergoing LITT for intracranial tumors/neoplasms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…Occasionally, GBM patients may not be candidates for surgical debulking of the tumor via an open craniotomy, and a relatively new technique known as ‘Laser Interstitial Thermal Therapy’ (LITT) is being trialed as a potential cytoreductive technique in destroying tumor cells via a localized elevated temperature [ 42 , 43 , 44 ]. It involves the insertion of an MRI-guided laser-tip probe into the tumor to deliver low-powered laser-induced thermotherapy.…”
Section: Therapeutic Strategies For Glioblastomamentioning
confidence: 99%
“…Occasionally, GBM patients may not be candidates for surgical debulking of the tumor via an open craniotomy, and a relatively new technique known as ‘Laser Interstitial Thermal Therapy’ (LITT) is being trialed as a potential cytoreductive technique in destroying tumor cells via a localized elevated temperature [ 42 , 43 , 44 ]. It involves the insertion of an MRI-guided laser-tip probe into the tumor to deliver low-powered laser-induced thermotherapy.…”
Section: Therapeutic Strategies For Glioblastomamentioning
confidence: 99%
“…Laser interstitial thermal therapy (LITT) has emerged as an alternative, minimal invasive neurosurgical technique for patients with epilepsy, tumors or radiation necrosis [ 1 ]. LITT has been proven to be useful for lesions located in difficult to access brain areas, in patients with a greater surgical risk or in the case of recurrence and repeated resections [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with unresectable glioblastoma could especially benefit from LITT, as LITT can be added to the standard adjuvant chemotherapy and radiotherapy to improve clinical outcomes. Previous studies have suggested that patients with nGBM have reasonable survival outcomes and complication rates when treated with LITT [ 1 , 2 , 3 , 4 , 5 , 7 , 9 , 10 ]. In addition, LITT is not bound to a maximum dose and can therefore be used multiple times [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication looking at outcome, 83.2% of patients were able to be discharged home after hospital stay of a mean of only 33.8 h and with a only 1.5% rate of serious adverse events or repeat hospitalization within 30 days of the procedure. [ 22 ] Longest length of hospital stay in this same study, however, was 29 days. Studies have shown that LITT treatment of deep-seated gliomas led to longer intensive care unit stays for delayed neurological recovery.…”
Section: Mrglitt For Malignant Tumorsmentioning
confidence: 60%